ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA PhET DI SMA BRAWIJAYA SMART SCHOOL MALANG - Sekar Indah Ret Noning Tiyas; Khusaini Khusaini; Anita Purwantini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The research aims to determine the improvement in learning outcomes by implementing the PBL model assisted by PhET media at SMA Brawijaya Smart School Malang. This type of quasi-experimental research with a one group pretest-posttest design. The population is all students in class XI-2 SMA Brawijaya Smart School Malang. The research subjects were 34 people consisting of 15 women and 19 men. The instrument used to collect data on cognitive learning outcomes in the research was 10 multiple choice questions with five validated options, while skills and activity learning outcomes were taken using assessment sheets through observer observation. From the results of data analysis, research findings were obtained on the application of the PBL model assisted by PhET media at SMA Brawijaya Smart School Malang, namely: Student learning outcomes using the PBL model experienced an increase in both cognitive, psychomotor and activity where cognitive increased from meeting I to II by 25% and from meeting II III increased by 30%. Student activities and skills by applying the PBL model increase in the active category. The results show that the application of the PBL model assisted by PhET media can improve student learning outcomes.